English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Solve using square root method:

9x^2-2=0

2006-11-10 16:41:34 · 13 answers · asked by rwwebber4 2 in Science & Mathematics Mathematics

13 answers

9x^2-2=0
Add 2 to both sides of the equation:
9x^2=2
Divide both side of the equation by 9:
x^2=.222222
Solve both sides for the square root:
x=.471404521

2006-11-10 16:50:00 · answer #1 · answered by cdb 3 · 0 0

9x^2=2 so x^2=2/9 x= (square root of 2)/3 or (minus square root of 2)/3

2006-11-11 01:07:36 · answer #2 · answered by peterwan1982 2 · 0 0

you question!

9X² - 2 = 0

=> 9X²=2
=>(3X)²=2

taking square root both sides.

√(3X)² = ±√2
3X = ±√2
X = ±(√2)/3

X= ±0.4714

so, X= + 0.4714 and X= - 0.4714

2006-11-11 02:03:57 · answer #3 · answered by Da Sahar SToRaY 2 · 0 0

Which square root method?
9x^2 - 2 = 0
x^2 = 2/9
x = (1/3)√2

.... 1. 4. 1. 4.. 2
....√2.00 00 00 00 00
.....-1
24 | 1 00
. 4 |... 96
.281 |.. 4 00
.... 1 |.. 2 81
2824 |...1 19 00
..... 4 |.. 1 12 96
28282 |...... 6 04 00
....... 2 |...... 5 65 64
28284 |........ 38 36

... and so forth ...

x = 1.4142/3 = 0.4714

2006-11-11 01:08:26 · answer #4 · answered by Helmut 7 · 0 0

You factor a - b as (√a + √b)(√a - √b). Thus,

9x² - 2 = 0



We factor this using the factoring

[√(9x²) + √(2)][√(9x²) - √(2)] = 0



We simplify

(3x + √2)(3x - √2) = 0



Thus,

3x + √2 = 0 or 3x - √2 = 0



Then,

3x = -√2 or 3x = √2



Therefore,

x = -√2/3 or x = √2/3



^_^

2006-11-11 06:33:14 · answer #5 · answered by kevin! 5 · 0 0

9x^2-2=0

first transpose -2 to the other side of the equation

9x^2 = 2

then divide both sides by the literal coeffient of x which is 9
9x^2 = 2
____ ___
9 9

x^2 = 2/9

squareroot of (x^2) = squareroot of 2/9

x = squareroot of 2 all over 3

2006-11-11 00:53:54 · answer #6 · answered by lazareh 2 · 0 0

simple quadratic.. solve it like a regular equation.. add the two over to the other side and youll get 9x^2=2.. divide by 9 x^2=9/2 square root--> squareroot(9/2 but you cant leave a fraction under a radical, so spit it up radical(9 over radical(2 multiply by radical(2 to get rid of the fraction, and youll get radical(18 over 2 reduce radical(18 into 3radical(2over 2

2006-11-11 00:49:34 · answer #7 · answered by Ryan C 2 · 0 0

Well usually when I use the square root method, also know as lupis rootis methodist, I find it best to start at Begnemin. I'm sure you are aware of the Begnemin Method. Very commonly used on Methodists. I myself am a Protestant. I like simple addition myself. Good luck, dear.

2006-11-11 00:47:24 · answer #8 · answered by Anonymous · 0 0

9x^2-2=0
add 2 to both sides
9x^2=2
divide both sides by 9
x^2=2/9
square root both sides
x=+/- (sqrt(2))/3

2006-11-11 00:59:06 · answer #9 · answered by Chris M 1 · 0 0

9x^2 - 2 =0
(3x+2)(3x-1) = 0

Thus...
3x+2 =0
3x =-2
x = -0.66

3x-1 =0
3x = 1
x = 0.33

Does this Help?

2006-11-11 00:54:14 · answer #10 · answered by Shadow 3 · 0 0

fedest.com, questions and answers